Dynamical structure factor of two-dimensional electrons over a helium film - Patricia Cristina Venturini; Nelson Studart; Jose Pedro Rino (Физика низких температур, 2008)
The dynamical structure factor of a two-dimensional electrons trapped to a helium film deposited on a solid substrate is determined through molecular dynamics simulations for different film thicknesses and two substrates. The phases of the system varying from the classical Wigner crystal to strong and intermediate- correlated electron liquid as well the influence of the film thickness and substrate are analyzed in the numerical experiments.